Convexity Subarachnoid Hemorrhage with PiB Positive Pet Scans: Clinical Features and Prognosis. Issue 3 (18th December 2014) - Ly, John V.; Singhal, Shaloo; Rowe, Christopher C.; Kempster, Peter; Bower, Simon; Phan, Thanh G.
ABSTRACT BACKGROUND Cerebral amyloid angiopathy (CAA) has been reported to present as convexity subarachnoid hemorrhage (cSAH). Lesser known is that cSAH can herald intracerebral hemorrhage (ICH) and ischemic lesions. We present seven new cases with 11C‐Pittsburgh compound B (PiB) positive positron emission tomography (PET) scans including two with biopsy, review the literature and comment on clinical and radiological findings. METHODS Patients with cSAH identified on CT, underwent MR imaging and MR angiography to exclude intracranial aneurysm. Nonaneurysmal cSAH were further prospectively evaluated for amyloid angiopathy using PiB. Clinical and radiological features of cSAH, subsequent ICH and ischemic lesions were characterized. RESULTS Seven patients with nonaneurysmal cSAH fulfilled the Boston criteria for probable CAA. All had PiB PET scans consistent with CAA. Of the 4 patients who had contrast MR Imaging all had enhancement overlying the cSAH, followed by ICH in three cases. All patients presented with transient sensory symptoms. All patients had small punctate subcortical and cortical infarcts on diffusion‐weighted MR imaging. Literature review revealed subsequent ICH in approximately 11/79 patients. CONCLUSION The finding of cSAH and PiB binding in our patients suggest underlying CAA. cSAH may be associated with ischemic lesion as well as future ICH occurrence.